Pengaruh Edukasi Tentang Pemanfaatan Teledentistry terhadap Peningkatan Pengetahuan Pegawai Puskesmas - Andayani, Lia H.; Nusantara, Mutiara A. (e-GiGi, 2025)
Abstract: The government of Indonesia has issued technical guidelines for dental and oral health services at first-level health facilities using teledentistry. Knowledge regarding teledentistry among health care workers in first-level health facilities, especially in community health centers has been considered essential. This study aimed to determine the effect of education regarding teledentistry on increasing the knowledge of Cipanas Community Health Center, Garut Regency. This quasi-experimental study involved 44 health care workers of the Health Center. The questionnaire used consists of 15 items which have been tested for validity and reliability. Pre-test was conducted before receiving material regarding the teledentistry in the form of power point text (PPT), meanwhile, post-test was conducted immediately after material delivery was completed. Paired Sample T-test was carried out to see the difference between pre-test and post-test scores. ANOVA test was carried out to evaluate the difference between pre-test and post-test scores based on respondent characteristics. There was a significant difference between pre-test mean score of 7.5 and post-test mean score of 12.3 (p=0.000). There was a significant difference between pre-test mean score based on educational level (p=0.028) and occupation (p=0.018). There was a significant difference between post-test mean score based on educational level (p=0.009). In conclusion, there is an increase in the knowledge of  healthcare workers of Cipanas Community Health Center after receiving educational material regarding teledentistry. Keywords: Covid-19; dentist; community health center; health workers; teledentistry    Abstrak: Pemerintah Indonesia telah mengeluarkan petunjuk teknis pelayanan kesehatan gigi dan mulut pada fasilitas kesehatan tingkat pertama (FKTP) dengan menggunakan teledentistry. Pengetahuan terkait teledentistry dianggap penting bagi tenaga medis dan tenaga kesehatan FKTP, terutama pusat kesehatan masyarakat (Puskesmas). Penelitian ini bertujuan untuk mengetahui pengaruh edukasi tentang teledentistry terhadap peningkatan pengetahuan pegawai Puskesmas Cipanas Kabupaten Garut. Studi kuasi eksperimental ini melibatkan 44 pegawai Puskesmas Cipanas Kabupaten Garut. Kuesioner yang digunakan terdiri dari 15 item yang telah diuji validitas serta reliabilitasnya. Pre-test diberikan sebelum mendapatkan materi mengenai teledentistry dalam bentuk power point text (PPT) sedangkan post-test dikerjakan segera setelah pemberian materi selesai.  Uji paired sample t-test dilakukan untuk melihat perbedaan nilai pre-test dan post-test. Hasil penelitian mendapatkan perbedaan bermakna antara rerata nilai pre-test sebesar 7,5 dan post-test sebesar 12,3 (p=0,000). Uji ANOVA menunjukkan perbedaan bermakna nilai rerata pre-test responden berdasarkan variabel tingkat pendidikan (p=0,028) dan pekerjaan (p=0,018). Terdapat perbedaan bermakna nilai rerata post-test responden berdasarkan variabel tingkat pendidikan (p=0,009). Simpulan penelitian ini ialah terdapat peningkatan pengetahuan pegawai Puskesmas Cipanas Kabupaten Garut setelah mendapatkan materi edukasi mengenai teledentistry. Kata kunci: Covid-19; dokter gigi; puskesmas; tenaga kesehatan; teledentistry